Ethics and Journalism in Central Asia: A Comparative Study of Kazakhstan, Kyrgyzstan, Tajikistan and Uzbekistan. Issue 1 (2nd January 2020) - Kurambayev, Bahtiyar; Freedman, Eric
ABSTRACT: Journalism faces a series of ethics crises, particularly in Central Asia because journalism is marked by wide ethical misbehavior including lack of balance and impartiality, using multiple fake names, selling and/or buying news, bribing journalists and others. This study analyzes professional ethical perspectives and practices of Central Asian journalists by examining and comparing the four former Soviet republics of Kazakhstan, Kyrgyzstan, Tajikistan, and Uzbekistan Table 1 . This study uses in-depth interviews with 24 journalists to examine their ethical ideals in the profession and how their ethical perspectives impact potential democracy. Its significance lies in revealing the gravity of ethical misbehavior where journalists call ethics a "Western luxury" and where public life was filled with falsehoods.